2011
DOI: 10.1088/1674-1056/20/12/128903
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in complex motor networks induced by Newman—Watts small-world connections

Abstract: Chaos in complex motor networks induced byNewman Watts small-world connections * Wei Du-Qu( ) a) † , Luo Xiao-Shu( ) a) , and Zhang Bo( ) b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Very recently, our investigation showed that the connection probability p in the NWSW motor networks can induce and enhance chaos [12]. Fig.…”
Section: Chaos In Complex Network Model Of the Pmsmmentioning
confidence: 82%
See 2 more Smart Citations
“…Very recently, our investigation showed that the connection probability p in the NWSW motor networks can induce and enhance chaos [12]. Fig.…”
Section: Chaos In Complex Network Model Of the Pmsmmentioning
confidence: 82%
“…Based on the Newman-Watts small-world (NWSW) connectivity, the motor networks can be written as follows [12], [24]:…”
Section: Chaos In Complex Network Model Of the Pmsmmentioning
confidence: 99%
See 1 more Smart Citation